2012
DOI: 10.1111/j.1600-0501.2012.02491.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, controlled clinical trial evaluating the clinical radiological and aesthetic outcome after 5 years of immediately placed implants in sockets exhibiting periapical pathology

Abstract: OBJECTIVE: The aim was to compare the clinical, aesthetic and radiological outcome of immediately placed implants in sockets with or without periapical pathology 5 years after placement. MATERIALS AND METHODS: Twenty-seven patients were followed 5 years after immediate implant placement (test-group: 12 patients with periapical pathologies; control-group: 15 patients without periapical pathology). Clinical (FMBS, FMPS, CAL, keratinized mucosa), aesthetical (length of clinical crown, Papilla index), and radiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(89 citation statements)
references
References 31 publications
5
83
0
1
Order By: Relevance
“…Ridge preservation procedures, originally intended to maintain bone volume after tooth extraction, have also shown some reduction in height and width . Jung et al (2013) using CBCTs showed a mean horizontal reduction of 0.6mm and a vertical reduction from 0.0 to 1.2mm at extraction sites filled with anorganic bovine bone with no flap elevation at 6 months of healing. Similarly, the results of this investigation show that immediate implant placement with simultaneous bone grafting does not entirely avoid bone resorption.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Ridge preservation procedures, originally intended to maintain bone volume after tooth extraction, have also shown some reduction in height and width . Jung et al (2013) using CBCTs showed a mean horizontal reduction of 0.6mm and a vertical reduction from 0.0 to 1.2mm at extraction sites filled with anorganic bovine bone with no flap elevation at 6 months of healing. Similarly, the results of this investigation show that immediate implant placement with simultaneous bone grafting does not entirely avoid bone resorption.…”
Section: Discussionmentioning
confidence: 93%
“…Placing immediate implants on sites with previous periapical pathologies has been a concerning issue but some recent studies have shown similar survival rates to those implants inserted in healthy areas (Jung et al 2013;Lindebom et al 2006). Hence, survival rates of 92-100% were reported in a recent systematic review (Corbella et al 2013).…”
Section: Immediate Implant Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…The result reflects and confirms the hypothesis that endosteal implants can be successfully integrated in infected sites. However, alveolar ridge resorption after the tooth extraction is a frequent occurrence and may significantly reduce the residual bone volume [23][24][25][26][27][28]. This study is a proof of principle that sockets can heal naturally with immediately placed implants in infected sites and tissue shrinkage can be reduced by utilizing least invasive surgical and prosthetic protocol.…”
mentioning
confidence: 76%
“…Nowadays, the replacement of single and multiple gaps in partially edentulous patients by means of dental implants is a predictable clinical procedure . Nevertheless, for patients undergoing single implant treatment in high‐demanding areas, the esthetic outcome may be more difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%